MEMBANGKITKAN JIWA WIRAUSAHA MUDA MELALUI UMKM P2MKP ALANG-ALANG TUMBUH SUBUR - Ulynnuha, Ovi Itsnaini; Aji, Nur Prasetyo; Arsyad, Hambali; Mirawati, Silvia Ayu; Mujiyati, Mujiyati (LPPM Institut Teknologi dan Bisnis Kristen Bukit Pengarapan, 2023)
The millennial generation now has a very big role in building the nation. The millennial generation's broad way of thinking can make changes and become pioneers, not only that but also able to create new things in society. Producing young entrepreneurs is certainly not something easy, because young entrepreneurs emerge from the determination of someone who has an entrepreneurial spirit and those who are confident, creative and innovative. Entrepreneurship is a strong belief that a person has in changing the world through ideas and innovation (Isabella and Loliyani, 2022). This belief is then followed up with the courage to take risks to realize his ideas and innovations. People who have this belief are called entrepreneurs. The entrepreneurial spirit must be instilled from an early age in the millennial generation. The millennial generation needs to be given regular assistance in order to foster an entrepreneurial spirit. In order to awaken the spirit of young entrepreneurs, several assistance efforts must be made in terms of business development, financial management, marketing and use of technology. Apart from that, this assistance can also help young entrepreneurs access capital and markets through partnerships with industry. The hope is that through community service it will be able to awaken the spirit of young entrepreneurs and help improve the regional economy, especially in Surakarta.